2017
DOI: 10.24252/nature.v4i2a8
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Best Practice Design Berdasar Hadits Sebagai Panduan Perancangan Arsitektur

Abstract: Abstrak_ Kajian berbagai disiplin ilmu dari sudut pandang keislaman telah banyak dilakukan, termasuk dalam bidang ilmu Arsitektur. Berbagai pendapat tentang bentuk Arsitektur Islam pun banyak bermunculan, baik yang memandang Arsitektur Islam dari sudut pandang tipologi fisik, filosofi hingga kondisi sosiodemografi. Akan tetapi di era modern dan heterogen saat ini bagaimana sebuah produk arsitektural dapat dikategorikan sebagai Arsitektur Islam masihlah menjadi perdebatan. Ketidakhadiran sebuah acuan dalam menj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
1
0
1
Order By: Relevance
“…Related to the respondents understanding about the relationship between architecture and Qur'an-Hadith, the findings were in line with what has been described by previous research on the correlation between Islamic teachings and architecture, both in theoretical and practical contexts [7]- [9]. The Qur'an and Hadith were present to ensure that "arrangements" made within the architecture were able to ensure the continuity of hablumminallah, hablumminannaas and hablumminal'alami [10].…”
Section: Figure 1 Respondent's Distribution By Originsupporting
confidence: 85%
“…Related to the respondents understanding about the relationship between architecture and Qur'an-Hadith, the findings were in line with what has been described by previous research on the correlation between Islamic teachings and architecture, both in theoretical and practical contexts [7]- [9]. The Qur'an and Hadith were present to ensure that "arrangements" made within the architecture were able to ensure the continuity of hablumminallah, hablumminannaas and hablumminal'alami [10].…”
Section: Figure 1 Respondent's Distribution By Originsupporting
confidence: 85%
“…Ketiga fasilitas yang dibutuhkan menunjukkan bahwa kesadaran jamaah akan pentingnya aktivitas pendidikan dalam fungsi masjid. Di samping itu, menurut Noe'man (dalam Ratodi & Hapsari, 2017), konsep perancangan bengunan berarsitektur islam, harus terkandung unsurunsur rahmatan lil alamin, berkiblat, beraturan, efisien, keindahan dalam kesederhanaan, silaturrahim, bersih, sehat, nyaman, dan berkelanjutan. Sementara itu, dalam konteks kekinian, di mana terjadi pandemi Covid-19, menurut Nasution & Wijaya (2020, p. 95), perlu adanya manajemen masjid berbasis health transition untuk mencegah penyebaran dan penularan virus seperti Covid-19.…”
Section: Pendahuluanunclassified
“…The dimensions are shown in Figure 1, Figure 2, and Figure 3. The dimensions of people standing praying who can close the shaf or line of prayer are 55-60 cm, with a prostration room of 120-130 cm [16]. It can be concluded that to make the activity of standing in prayer can form a tight line.…”
Section: Introductionmentioning
confidence: 99%